When SAMS Met "ad hoc": Work Organization and Stress at ODSP - Lewchuk, Wayne (Ontario Public Service Employees Union, 2016)
This report is a study of occupational health and safety conditions at Ontario Disability Support Program (ODSP) offices in the wake of two sets of changes: The reorganization of work associated with the Modernized Service Delivery Model (MSDM) introduced in 2010 (commonly referred to as Modernization), and the 2014 implementation of the Social Assistance Management System, a new computer system knowns as SAMS. As I crossed Ontario interviewing ODSP workers and read dozens of pages of comments workers added to their online survey, I heard and read numerous stories of frustration and disappointment with the changes, frustrations that were negatively affecting the health of workers. However, I also heard how many ODSP workers had been looking forward to these changes.